Renaissance Europe : individual and society, 1480-1520 - Hale, J. R. (University of California Press, 1977)
This classic history examines the political, economic, social, religious and cultural life of Europe at the height of the Renaissance. J.R. Hale not only records the events of 1480-1520, but also suggests what it was like to have lived in this period. He provides readers with an understanding of the quality of lives of people living at this time and includes processes and personalities not often covered by other books. For the second edition Professor Michael Mallet provides an updated bibliography and an extended introduction explaining the book's place in the historiography of the subject. The book is arranged thematically, each chapter designed to provide information about a specific field of inquiry and also give an insight into the people of this era. J. R. Hale investigates how these people felt about their environment and the passage of time; their relationships with government and other institutions, from the Church to the family; their economic frameworks; the part religion played in their lives; and what cultural and intellectual pursuits were available to them. Renaissance Europe compares our own attitudes to those of the Renaissance and vice versa, thereby enriching the readers understanding of everyday life in the past.